Production and marketing problems of small and medium scale industries in Sarawak (A case study) / Ibrahim Shah ... [et al.] - Shah, Ibrahim; Yap, Yin; Amin, Nicholas (Institut Teknologi Mara Cawangan Sarawak, 1990)
Small and Medium Scale Industries have generated considerable interests among the academicians, the politicians and business sectors in the country. This is particularly evident from the numerous studies, various incentives and debates about them that have taken place lately in Malaysia. This keen interest is attributed to the fact that SMIs are regarded as the source of employment opportunities. They inspire entrepreneurs to become pioneers. SMIs also have potential roles to play in the developing economy. To date, however, there has not been any complete and serious study of the role of SMIs in Sarawak though data have been collected in the field. However, no in-depth analysis has been carried out so far. In an attempt to explore the situation currently prevailing in Sarawak, a study has been commissioned by the newly established Ministry of Industrial Development, Sarawak with the joint effort of MARA Institute of Technology, Sarawak Branch in 1989.